3D reconfigurable antenna - Abdul Malek, Norun; Seager, Rob (2010)
A simple programming technique (MATLAB) has been written for the analysis of a beam reconfigurable antenna array. The technique is based on the calculation of mutual impedance using Induced EMF method. This can be applied to an array of dipoles arranged in various configurations. An array of 12 dipoles has been positioned at the edge of a cube structure to demonstrate this behavior. The size of the cube is (0.6533lamda)3m3. Beams may be focused in different directions by turning On (feeding) one or more dipoles while the rest remain short-circuited (Off). The results match with simulation software such as NEC and EMPIRE XCcel.